The prognostic impact of FLT3-ITD and NPM1 mutations in patients with relapsed acute myeloid leukemia and intermediate-risk cytogenetics - How, J (Nature Publishing Group, 2013)
Internal tandem duplication of the fms-like tyrosine kinase-3 gene (FLT3-ITD) and nucleophosmin-1 (NPM1) mutations have prognostic importance in acute myeloid leukemia (AML) patients with intermediate-risk karyotype at diagnosis, but less is known about their utility to predict outcomes at relapse. We retrospectively analysed outcomes of 70 patients with relapsed, intermediate-risk karyotype AML who received a uniform reinduction regimen, with respect to FLT3-ITD and NPM1 mutation status and first complete remission (CR1) duration. CR1 duration, but not molecular status, was significantly correlated with CR2 rate. On univariate analysis, patients with mutated FLT3-ITD (FLT3+) had significantly worse overall survival (OS) compared with those with neither an NPM1 nor FLT3-ITD mutation (NPM1-/FLT3-). On multivariate analysis, shorter CR1 duration was significantly correlated with inferior OS at relapse (P<0.0001), while FLT3 and NPM1 mutation status and age were not significantly correlated with OS. Patients who subsequently underwent allogeneic stem cell transplant (alloSCT) had a superior OS regardless of CR1 duration, but outcomes were better in patients with CR1 duration>12 months. In intermediate-risk karyotype AML patients receiving reinduction, CR1 duration remains the most important predictor of OS at relapse; FLT3-ITD and NPM1 status are not independent predictors of survival.